Justice warrior - Davis, Rusty (Waterville, Maine Thorndike Press, a part of Gale, a Cengage Company, 2023)
"Montanas Tongue River Valley is a cauldron of animosity between the Northern Cheyenne who are trying to endure, and land-hungry settlers and others who want them wiped out once and for all. Two men become the focal point for keeping peace-John Dooley and his Cheyenne co-worker Fox Running. The friends must solve two murders that could ignite the powder keg of emotions. They face the gravest test of their friendship yet as Dooley, new to the West, seeks moderation while Fox Running-who lost his family and home in an 1876 army raid-can see only fighting. Fox Running turns to Cut Sky, the sharpshooting daughter of an Indian known as the Bandit King, as he tries to become the Justice Warrior of the Cheyenne. The enemy have money and guns; the Cheyenne have their spirit friends and a will to resist. From a showdown on the streets of a cowboy town to a daring last-ditch fight, Fox Running fights for justice as his friends fight to keep him alive" --
111430
Keywords: Murder -- Investigation -- Fiction; Indians of North America -- Montana -- Fiction; Large type books; Northern Cheyenne Indian Reservation (Mont.) -- Fiction; Novels; Large print books; Western fiction